2021
DOI: 10.1111/ppc.12726
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acceptance and commitment therapy orientated anger management training on anger ruminations and impulsivity levels in forensic psychiatric patients: A randomized controlled trial

Abstract: Purpose This study aimed at determining the effect of acceptance and commitment therapy (ACT) orientated anger management training on levels of anger rumination and impulsivity in people receiving forensic mental healthcare. Design and Methods This was a randomized controlled study. The research data were collected between July 2018 and February 2019. The personal information form, Anger Rumination Scale, and Barratt Impulsiveness Scale were used for data collection. Findings Total scores on the Barratt Impuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The content validity of the Anger Rumination Scale was assessed by the judgment of ten psychology experts, and Kendall's agreement coefficients for the total anger rumination scale, angry afterthoughts, vengeful thoughts, angry memories, and understanding of causes were calculated as 0.70, 0.82, 0.79, 0.70, and 0.78, respectively. The convergent and discriminant (differential) validity of the Anger Rumination Scale was confirmed through simultaneous administration of the Tehran Multidimensional Anger Scale and the Mental Health Scale on participants (Polat & Asi Karakaş, 2021;Teymouri et al, 2020).…”
Section: Anger Ruminationmentioning
confidence: 87%
See 2 more Smart Citations
“…The content validity of the Anger Rumination Scale was assessed by the judgment of ten psychology experts, and Kendall's agreement coefficients for the total anger rumination scale, angry afterthoughts, vengeful thoughts, angry memories, and understanding of causes were calculated as 0.70, 0.82, 0.79, 0.70, and 0.78, respectively. The convergent and discriminant (differential) validity of the Anger Rumination Scale was confirmed through simultaneous administration of the Tehran Multidimensional Anger Scale and the Mental Health Scale on participants (Polat & Asi Karakaş, 2021;Teymouri et al, 2020).…”
Section: Anger Ruminationmentioning
confidence: 87%
“…The intervention protocol for this study, focusing on emotion-focused therapy (EFT) aimed at enhancing assertiveness and reducing anger rumination in women victims of domestic violence, unfolds over nine sessions (Firoozeh et al, 2021;Piquero et al, 2021;Polat & Asi Karakaş, 2021;Saeidi et al, 2020):…”
Section: Emotion-focused Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Our results were in line with Polat & Karakaş (2021), who conducted a randomized control trial to examine the impact of ACT therapy-oriented anger management training on anger rumination and impulsivity levels in individuals receiving forensic mental healthcare. They discovered that the experimental group’s total scores on the Barratt Impulsiveness and Anger Rumination Scales were significantly lower than those of the control group [ 38 ]. In this context, Baghani & Akbari (2020) confirmed that cognitive defusion, the effect of thought (such as the desire to use) on behavior in acceptance and commitment therapy, can explain why ACT therapy effectively reduces the impulsivity components of women who abuse drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A single‐case study by Moeller et al (2021) substantively portrays the application of a rumination‐focused CBT for anger with a schizotypal patient, obtaining meaningful clinical change in anger scores and in violent imagery, although not in anger rumination scores. However, a recent randomized controlled trial by Polat and Karakas (2021), conducted with forensic patients receiving acceptance and commitment therapy, obtained significant and substantial reductions in anger rumination in the anger treatment condition. Given that forensic populations and other long‐term care patients likely have traumatic life histories in which anger schemas and aggressive behavior scripts have been formed, there is much to be gained in the amelioration of their anger ruminative routines.…”
Section: Discussionmentioning
confidence: 99%